Teaching English to Young Learners Abroad: Indonesian Pre-Service Teachers’ Challenges in Thailand - Siti Aisyah Mahmud Yunus; Zulhermindra; Suyono; Deni Asrida (FOSTER: Journal of English Language Teaching, 2026)
This study investigates the challenges faced by pre-service teachers in teaching English in Thailand’s elementary schools. Although previous studies have examined Teaching English to Young Learners (TEYL), limited research has specifically explored how pre-service teachers experience and navigate challenges in international teaching contexts. This study employed a qualitative case study design involving eight pre-service teachers from UIN Mahmud Yunus Batusangkar who participated in the International Pre-Service Teaching Program in Thailand. Data were collected through in-depth interviews and analyzed using Miles and Huberman’s (1984) interactive model, including data reduction, data display, and conclusion drawing. The findings revealed three categories of challenges. First, challenges related to learners include cognitive development difficulties, multi-level groups, discipline problems, low focus, lack of motivation, speaking problems, and writing problems. Second, challenges related to pre-service teachers themselves include limited use of technology, lack of professional development, inadequate use of teaching English to young learners (TEYL) methods, difficulty understanding teaching materials, and issues of teacher professionalism. Third, challenges related to the teaching context include language differences, insufficient facilities, curriculum or syllabus issues, lack of mentor support, and cultural differences. Beyond identifying these categories, this study shows that these challenges are interconnected, where linguistic barriers and contextual constraints influence classroom interaction, instructional decisions, and teacher confidence. The findings imply that teacher education programs need to strengthen practical preparation, particularly in classroom management, TEYL pedagogy, cross-cultural communication, and teaching in low-resource environments. This study contributes to the literature by providing empirical insights into the complexity of pre-service teachers’ experiences in international teaching contexts.